Morbidity associated with overweight and obesity in health personnel: a 10-year retrospective of hospital-based cohort study in Taiwan - Yeh TL; Chen HH; Chiu HH; Chiu YH; Hwang LC; Wu SL (Diabetes, Metabolic Syndrome and Obesity, 2019)
Tzu-Lin Yeh,1,2 Hsin-Hao Chen,1 Hsiao-Hui Chiu,3 Yu-Hua Chiu,4 Lee-Ching Hwang,5,6 Shang-Liang Wu7 1Department of Family Medicine, Hsinchu MacKay Memorial Hospital, Hsinchu City, Taiwan; 2Institute of Epidemiology and Preventive Medicine, College of Public Health, National Taiwan University, Taipei, Taiwan; 3Department of Nursing, Taipei Veterans General Hospital, Taipei City, Taiwan; 4Occupational Safety and Health Office, Taipei Veterans General Hospital, Taipei City, Taiwan; 5Department of Family Medicine, MacKay Memorial Hospital, Taipei, Taiwan; 6Department of Medicine, MacKay Medical College, New Taipei City, Taiwan; 7School of Medicine, Griffith University, Gold Coast Campus, QLD, Australia Purpose: To investigate morbidity associated with overweight and obesity in health personnel and compare the differences among work roles.Materials and methods: This retrospective cohort study examined measurements obtained during employee medical checkups between 2007 and 2016 in a Taiwan medical center. BMI was used to define overweight (≥24 and <27 kg/m2) and obesity (≥27 kg/m2). Morbidity refers to prevalence, period incidence proportion, and incidence rate. Multivariable Cox model was used to estimate the HRs and 95% CI of the incidence proportion across work roles. Results: Ten thousand six hundred fifty-one health personnel with 24,295 BMI measurements were recruited. Mean age was 33.4±10.7 years and 72.4% was female. In total, 1,992 (8.2%) health personnel were underweight, 13,568 (55.8%) had a normal BMI, 5,097 (21%) were overweight, and 3,638 (15%) were obese. Five thousand nine hundred one health personnel with 31,172 different interval-year arrangement combinations were obtained. The incidence proportion of overweight and obesity was 1,947 (6.2%) and 1,494 (4.8%), respectively. The incidence rate was 37/1,000 and 15/1,000 person-years, respectively. Compared with that in supporting staff, the HR of overweight in doctors, nurses, and allied health professionals was 0.93 (95% CI =0.73–1.18, P=0.553), 0.92 (95% CI =0.73–1.16, P=0.491), and 0.85 (95% CI =0.67–1.09, P=0.202), respectively. Similarly, the HR of obesity was 0.86 (95% CI =0.66–1.14, P=0.301), 0.89 (95% CI =0.67–1.18, P=0.430), and 0.84 (95% CI =0.63–1.13, P=0.248), respectively.Conclusion: In health personnel, the prevalence of overweight and obesity was 21% and 15%, respectively. The incidence proportion was 6.2% and 4.8%, respectively. Morbidity across the four health work roles examined was not significantly different. Keywords: prevalence, incidence, obesity, overweight, health personnel, body mass index